The Influence of The Asean Regional Capital Market on Asean-5 Countries’ Foreign Exchange Reserves - Mulatsih, Srie Nuning; Masruri, Masruri; Subiyantoro, Heru; Yolanda, Yolanda (Jurnal Indonesia Sosial Sains, 2023)
The capital market sector is one area of economic activity that is expected to grow significantly following the adoption of the ASEAN Economic Community (AEC). As a result, integrating capital market activity in the ASEAN area must be a top priority in AEC implementation. The essential criterion for creating a seamless flow of cash and investment is the integration of ASEAN countries' capital markets. The total worth of all outstanding shares based on their normal closing price is reflected in the stock market capitalisation. A rise in the value of market capitalization indicates that the capital market is expanding. Capital flows into and out of the capital market are thought to have altered the value of foreign exchange reserves. Foreign capital market investment contributes to a balanced balance of payments. Foreign capital not only serves to cover the deficit in domestic capital that domestic savings cannot fill, but it also helps to fill the emptiness in the foreign exchange gap through asset sales.